A lyrical Architecture (Itinera, 2023)
The article investigates the relationship between architecture and opera and shows that this performative practice is contributing to modifying the approach in architectural design in the direction of overcoming the traditional separation between scenography and urban planning. Two contemporary examples and a genealogical case are proposed, in order to demonstrate that the relationship between architecture and opera maintains an “inescapable” tendency to build consensus, to which is added today a loss of mythopietic potential.
Keywords: Opera, architectural ephemera, scenography